Achievement of Traceability for DC Voltage and Current Measurements up to 5 kV and 1 A - M.Abdelmegeed, Hala; Halawa, Mamdouh; M. Aladdin, Omar (International Journal of Engineering and Technology, 2018)
National Institute of Standards is the National Metrology Institute of Egypt, which realizes units of measurements according to the Interna-tional System of Units. The DC Josephson Voltage Standard is used as a primary standard to reproduce the unit of volt and provide tracea-bility of measurements to the SI units. JVS, Zener diode reference standards, standard resistors, multifunction calibrators and voltage divid-ers of NIS maintain the DC voltage & current and provide the traceability to all Egyptian industrial governmental and private sectors. In this paper, the measurements' traceability of DC voltages from 10 mV up to 5 kV and DC currents from 100 Î¼A up to 1 A has been achieved. In this method, the Fluke 5720A multifunction calibrator has been calibrated in its DC voltage and current functions to cover the range of 1 kV and 1 A. To extend the voltage range to 5 kV, a universal high voltage divider has been used. The DC voltage calibrations have been performed using a Fluke 732B Zener diode reference standard, which is traceable to International System of Units via the NIS DC voltage primary standard. Relevant DC voltage and current measurements, associated with their expanded uncertainties, are presented in this work.Â Â